PENGARUH PAD, DANA PERIMBANGAN, JUMLAH PENDUDUK, DAN LLPDS PADA KABUPATEN/KOTA DI PROVINSI NTT - Nadia Taruk, Monika Alberta (Universitas Udayana, 2025)
Fiscal independence is one of the main indicators of the success of fiscal decentralization in Indonesia. Through fiscal decentralization, local governments are given the right to manage revenue, spend budgets, and formulate financial policies independently in order to meet the needs of their communities effectively and efficiently. However, East Nusa Tenggara Province still faces challenges in achieving fiscal autonomy due to its high level of dependence on central government transfers. Therefore, this study aims to examine the effect of PAD, balancing funds, population, and other legal income on regional spending in regencies/cities in East Nusa Tenggara Province from 2020 to 2024, both simultaneously and partially, using multiple linear regression analysis. Using panel data from regencies/cities in East Nusa Tenggara Province for the period 2020-2024 and the common effect model (CEM) method, it was found that the variables of PAD, balancing funds, population, and other legitimate income have a significant simultaneous effect on regional expenditure. Meanwhile, partially, the variables of PAD, balancing funds, and other legitimate income are positively related and have a significant effect, but the variable of population does not have a significant effect on regional expenditure. The regional government is expected to continue to optimize the potential of local revenue sources by strengthening PAD and increasing the efficiency of public spending to achieve sustainable fiscal independence in East Nusa Tenggara.